2020
DOI: 10.1186/s12870-020-2328-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of DRIK1, a stress-responsive receptor-like pseudokinase, reveals the molecular basis for the absence of ATP binding

Abstract: Background: Plants reprogram metabolism and development to rapidly adapt to biotic and abiotic stress. Protein kinases play a significant role in this process by phosphorylating protein substrates that activate or inactivate signaling cascades that regulate cellular and metabolic adaptations. Despite their importance in plant biology, a notably small fraction of the plant kinomes has been studied to date. Results: In this report, we describe ZmDRIK1, a stress-responsive receptor-like pseudokinase whose express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that Arabidopsis-derived STRUBBELIG ( SUB ) is classified within the SRF family and encodes an atypical kinase, often referred to as a pseudokinase due to the absence of one or more key residues essential for phosphoryl transfer 39 , 45 47 . Sequence alignment revealed that like SUB, OsSRF8 harbors amino acid alterations in the conserved positions crucial for kinase activity, such as E474M in the C-helix, D556N in the HRD motif, and D574H in the DFG motif (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Arabidopsis-derived STRUBBELIG ( SUB ) is classified within the SRF family and encodes an atypical kinase, often referred to as a pseudokinase due to the absence of one or more key residues essential for phosphoryl transfer 39 , 45 47 . Sequence alignment revealed that like SUB, OsSRF8 harbors amino acid alterations in the conserved positions crucial for kinase activity, such as E474M in the C-helix, D556N in the HRD motif, and D574H in the DFG motif (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, energy optimization was carried out using 2500 steps of steepest descent method and 2500 steps of conjugate gradient method. The system was then subject to 100 ps of NVT ensemble simulation and 100 ps of NPT equilibrium simulation under the condition of maintaining a temperature of 298.15 K. Finally, a 100 ns NPT ensemble simulation was performed under periodic boundary conditions, calculating long‐range electrostatic interactions using the PME method, a non‐bonded cut‐off distance set to 1 nm, a collision frequency set to 2 ps, system pressure of 101.325 kPa, integration step of 2 s and trajectory saved every 10 ps [31,32] …”
Section: Methodsmentioning
confidence: 99%
“…The system was then subject to 100 ps of NVT ensemble simulation and 100 ps of NPT equilibrium simulation under the condition of maintaining a temperature of 298.15 K. Finally, a 100 ns NPT ensemble simulation was performed under periodic boundary conditions, calculating long-range electrostatic interactions using the PME method, a non-bonded cut-off distance set to 1 nm, a collision frequency set to 2 ps, system pressure of 101.325 kPa, integration step of 2 s and trajectory saved every 10 ps. [31,32] Using molecular dynamics simulation, the binding free energy between a protein and a molecule was calculated. This calculation enables a deeper understanding of their interaction mechanism, which can contribute to drug design and treatment.…”
Section: Molecular Dynamics Simulations and Mm/gbsa Free Energy Calcu...mentioning
confidence: 99%